Potential of Triticale (X Triticosecale Wittmack) Malts for Beer Wort Production. (2nd October 2019) - Ambriz-Vidal, Tania N.; Mariezcurrena-Berasain, Maria D.; Heredia-Olea, Erick; Pinzon Martinez, Dora L.; Gutierrez-Ibañez, Ana T.
Abstract: Triticale grain, a wheat-rye hybrid mostly used for animal feed, has been recently reported to exhibit different trends when used as unmalted or malted grain in the brewing industry. The aim of this study was to evaluate the potential of four different triticale lines to evaluate their potential for malt production. The four studied triticale malts PM-1, PM-3, PM-6, and PM-8 lines yielded an extract content higher than 100% and a diastatic power similar to some barley malts (86.19–190.19°L). The produced worts showed a higher percentage of soluble protein, between 4.56% and 5.66%, with a large viscosity value (∼2.055 cP) reported for this raw material. Two triticale malts were selected based on their performance, PM-1 and PM-3, and fermented at different percentage combinations with barley malt (0, 30, 50, 70, and 100%). The results revealed that the use of 100% triticale malt yielded an acceptable fermentation, with an Apparent Attenuation Limit (AAL) of 72%. The optimal triticale-barley malt ratio was 30/70, where supplementing triticale malt enriched the extract, enhancing the fermentation. These results support the suitability and possible establishment of triticale grain as a brewing crop.